Grant Tambling interviewed by Peter Read in the Peter Read collection of interviews conducted for his book entitled, Charles Perkins : a biography - Tambling, G. E. (Grant Ernest), 1943-; Read, Peter, 1945- (1989)
Senator Tambling speaks about the shortcomings of ATSIC; the need for the involvement of state and territory governments; Perkins' sacking; the pressures on Perkins; selling ATSIC to the communities; the pressure on the Democrats to accept ATSIC; land rights; the need for outstations; the pressures on tribal aborigines; the impact of TV on society; criticism of Perkins in the Northern Territory; his first meeting with Perkins; his relationship with Perkins; Perkins' ability to ride out rough criticisms to achieve dialogue with anyone in the community.
Aboriginal and Torres Strait Islander people are advised that this recording may contain names and voices of deceased persons.
Digital master available
Senator Tambling has been the Federal Shadow Minister for Housing, External Territories and Northern Development since 1994, and Senator (Country Liberal Party) for the Northern Territory since 1987. He was also Member of the Northern Territory House of Representatives, 1980-1983.
Keywords: Tambling, G. E. -- 1943- -- Interviews; Perkins, Charles, -- 1936-2000.; Australia. -- Aboriginal and Torres Strait Islander Commission